Efektifitas Model Pembelajaran Diferensiasi Untuk Meningkatkan Motivasi Mahasiswa Dalam Mata Kuliah Kebugaran Jasmani - Nur Indah Atifah Anwar; Akbar Syafruddin (Indonesian Journal of Physical Activity, 2024)
This study is an experiment that aims to increase student motivation through the implementation of a differentiation learning model in physical fitness courses. The population in this study were students of the Faculty of Sport Sciences, Makassar State University with a sample size of 37 students. The sampling technique was carried out using a random sampling technique. The data collection technique was carried out using a motivation questionnaire with a Crinbach's Alpha reliability value of 0.960. The questions consisted of 20 items with 5 (five) answer choices. The data analysis technique was carried out using the t-test and the N-Gain test which aimed to determine the extent to which the implementation of the differentiation learning model was effective in increasing student motivation in following the lecture process. Based on the results of the effectiveness test, the maximum value was 89.29; the minimum value was 52.63; and the average value was 75.6. Based on these average values, it can be concluded that the implementation of the differentiation learning model is quite effective in increasing student learning motivation in physical fitness lectures.